Maternal and umbilical cord blood subfatin and spexin levels in patients with gestational diabetes mellitus - Yavuzkir, Seyda; Ugur, Kader; Deniz, Rulin; Ustebay, Dondu Ulker; Mirzaoglu, Miyase; Yardim, Meltem; Aydin, Suleyman (Elsevier Science Inc, 2020)
Subfatin and spexin are two novel adipokines implicated in glucose homeostasis. This study was designed to investigate changes in blood subfatin and spexin levels during gestational diabetes mellitus (GDM) and childbirth, and define the mechanisms of these hormones in the physiopathology of GDM. A total of 60 pregnant women, comprising 30 diagnosed with GDM and 30 with normal gestation, were included in the study. The diagnosis of GDM was made through a 75-g oral glucose tolerance test (OGTT) administered between 24 and 28 weeks of pregnancy. The amounts of subfatin, spexin, and insulin were measured in blood samples by enzyme-linked immunosorbent assays; lipid profiles, glucose, and other biochemical parameters were measured by using an autoanalyzer. Levels of subfatin and spexin were significantly higher in blood samples drawn at baseline (before OGTT) in mothers with GDM compared to those with normal gestation. Similar observations were made in maternal and cord blood sampled at the end of pregnancy. However, at delivery, the increase in subfatin and spexin concentrations observed at baseline was abrogated in both groups of pregnant women, although levels in mothers with GDM were comparatively higher. These results show that levels of subfatin and spexin increased because of GDM and suggest that these hormones could be potential biomarkers for the diagnosis and management of GDM.
Keywords: Subfatin; Spexin; Gestational diabetes mellitus; Adipokine